Efficacy of pillar suture for post-tonsillectomy morbidity in children: a meta-analysis - Kim,Ji-Sun (2021)
Abstract Introduction: Several surgical techniques have been used during tonsillectomy to reduce complications. Objectives: To assess the effects of pillar suture in conjunction with tonsillectomy as compared to tonsillectomy without suture in children. Methods: Two authors independently searched five databases (PubMed, SCOPUS, Embase, the Web of Science, and the Cochrane database) for studies published as recent as December 2018. Of the included studies, we compared tonsillectomy and pillar suture in combination (suture groups) with tonsillectomy alone,without suture, (control group). Postoperative pain intensity and other morbidities (e.g., postoperative bleeding, palatal hematoma, discomfort, and pillar edema) were measured during the postoperative period. Results: Postoperative bleeding [primary (OR = 0.47 [0.27; 0.81]) and secondary (OR = 0.14 [0.02; 0.78]) were significantly decreased in the pillar suture group compared to the control group. There were no significant differences between the two groups in postoperative pain at day 7 (SMD = −0.39 [−0.79; 0.00]), palatal hematoma (OR = 5.00 [0.22; 112.88]), palatal discomfort sensation (OR = 2.62 [0.60; 11.46]), site infection (OR = 5.27 [0.24; 113.35]), and velopharyngeal insufficiency (OR = 2.82 [0.11; 74.51]). By contrast, pillar edema (OR = 9.55 [4.29; 21.29]) was significantly increased in the pillar suture group compared to the control group. Conclusions: Pillar suture combined with tonsillectomy may reduce postoperative bleeding incidence despite increasing pillar edema in pediatric tonsillectomy. Postoperative pain-relief, palatal hematoma, palatal discomfort sensation, site infection, and velopharyngeal insufficiency were not significantly altered compared to tonsillectomy alone. However, further studies are needed to corroborate the results of this study.